2011
DOI: 10.1007/s00405-010-1475-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, observational study using rabeprazole in 455 patients with laryngopharyngeal reflux disease

Abstract: The role of proton pump inhibitor in the treatment of laryngopharygneal reflux disease (LPRD) has been advocated, but there has been few reports dealing with large population based on time-related efficacy of rabeprazole. It was designed to assess the efficacy of rabeprazole and to evaluate which symptoms or findings varied significantly as medication sustained. Multiorgan, open-label cohort, prospective observational study was designed. We identified 1,142 patients with LPRD, and enrolled 455 patients, who pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 30 publications
(32 reference statements)
7
59
0
2
Order By: Relevance
“…As such, we administered the RSI to our patients and found that 33.9% of pre-operative thyroidectomy patients had concomitant laryngopharyngeal reflux, which is in keeping with reported LPR rates in the general population [9][10][11]. However, when we looked specifically at the relative contribution of LPR to voice and swallowing complaints in this cohort we found that laryngopharyngeal reflux may account for a larger proportion of patients with elevated symptom scores.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…As such, we administered the RSI to our patients and found that 33.9% of pre-operative thyroidectomy patients had concomitant laryngopharyngeal reflux, which is in keeping with reported LPR rates in the general population [9][10][11]. However, when we looked specifically at the relative contribution of LPR to voice and swallowing complaints in this cohort we found that laryngopharyngeal reflux may account for a larger proportion of patients with elevated symptom scores.…”
Section: Discussionmentioning
confidence: 49%
“…Due to the non-specific nature of these complaints, and the possibility of other underlying etiologies, the true prevalence of voice and swallowing symptoms due to thyroid pathology remains unclear. These same symptoms are common in the general population, and are often attributed to and relieved with treatment for laryngopharyngeal reflux (LPR) [9][10][11]. Currently there is very limited literature examining the prevalence of laryngopharyngeal reflux in thyroidectomy patients.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a recent non placebo-controlled study showed PPI efficacy of improving LPR (including globus) symptoms and signs using large scaled patients 12. In addition, few data on clinical predictors of symptom response to PPIs in patients with globus has been reported.…”
Section: Introductionmentioning
confidence: 95%
“…According to some U.S. reports, LPRD affects approximately 10% of outpatients of the ear, nose, and throat (ENT) department consultation and up to 50% of patients in the voice center . The most common complaints related to LPRD include hoarseness, sore throat, odynophagia, cough, throat clearing, globus sensation, and excessive phlegm . Usual gastroesophageal reflux disease (GERD) findings such as heartburn, regurgitations, and esophagitis do not necessarily concern the majority of patients, leading some otolaryngologists to distinguish LPR and GERD as two different clinical entities .…”
Section: Introductionmentioning
confidence: 99%